A comparative analysis of multidimensional computerized adaptive testing for the DASH and QuickDASH scores in Dupuytren's disease. (July 2022) - Harrison, Conrad; Clelland, Andrew D.; Davis, Tim R. C.; Scammell, Brigitte E.; Zhang, Weiya; Russell, Peter; Fullilove, Sue; Chakrabarti, Indranil; Davidson, Dominique; Rodrigues, Jeremy
The QuickDASH is a short-form version of the DASH questionnaire, the most widely used patient-reported outcome measure in hand surgery. Multidimensional computerized adaptive testing (MCAT) can produce shorter and more precise testing than static short forms, like QuickDASH. We used DASH responses from 507 patients with Dupuytren's disease to develop a MCAT. The algorithm was evaluated in a Monte Carlo simulation, where the standard error of measurement (SEm) of scores obtained from the 11-item QuickDASH was compared with scores obtained from an MCAT that could administer up to 11 items from the full 30-item DASH. The MCAT asked a mean of 8.51 items (SD 2.93) and 265/1000 simulated respondents needed to complete ≤five items. Median SEms were better for DASH MCAT: 0.299 (hand function) and 0.256 (sensory symptoms) versus 0.320 and 0.290, respectively, for QuickDASH. Our study showed that the DASH MCAT can produce more precise DASH measurement than the QuickDASH, from fewer items.